New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean - Martins, Luciana; Tavares, Marcos (Zootaxa, 2018)
Two new species in the genera Thyone and Havelockia are described and illustrated based upon specimens collected from off the southeastern Brazilian coast. Thyone florianoi sp. nov. is characterized by having two pillared body wall tables with four-holed discs and introvert with multilocular tables. Thyone crassidisca is recorded herein for the first time from the South Atlantic Ocean (Brazil). Havelockia mansoae sp. nov. is distinctive in having two pillared body wall tables with four-holed discs and introvert with plates. This is the first record of the genus Havelockia from Brazilian waters.